2021
DOI: 10.1007/s13670-021-00359-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Alcohol use Disorder among Older Adults

Abstract: Purpose of Review The prevalence of alcohol use disorder (AUD) among older adults in the United States is rising, but remains underdiagnosed, underreported, and inadequately managed. This review highlights the medical, social, and cultural factors of AUD in older adults and provides guidelines for its screening, evaluation, and management. Recent Findings The COVID-19 pandemic has created additional challenges and barriers to care, as older adults may have disproportionate worsening of anxiety, depression, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the characteristics of AUD identified by conventional screening tools such as CAGE, AUDIT, or mean corpuscular volume may not be entirely generalizable to older individuals. [18] , [19] , [20] , [21] , [22] Hence, there is a need for screening methods specifically tailored to the elderly population that can effectively identify AUD in this demographics. As previous studies have suggested, treatment for AUD can be advantageous for older individuals, similar to their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the characteristics of AUD identified by conventional screening tools such as CAGE, AUDIT, or mean corpuscular volume may not be entirely generalizable to older individuals. [18] , [19] , [20] , [21] , [22] Hence, there is a need for screening methods specifically tailored to the elderly population that can effectively identify AUD in this demographics. As previous studies have suggested, treatment for AUD can be advantageous for older individuals, similar to their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The CAGE screening scores range from zero (negative responses to the four screening questions) to a maximum score of four (positive responses to all four screening questions). A positive response to any of the four questions may indicate alcohol misuse (Joshi et al, 2021). A CAGE score of two or more is considered clinically significant and a positive screening (Ewing, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…In many cases, alcohol misuse in older adults is underdiagnosed with improper assessment and management 43,44 . In fact, of those who admitted to having ongoing alcohol misuse in the UKB cohort, only 12.5% of these patients had any alcohol-related F.10 ICD-10 code (Supplementary Figure 4).…”
Section: Forecasting Older Adult Alcohol Misuse Using the Validated R...mentioning
confidence: 99%